ChemInform Abstract: Synthesis of Bis(indolyl)methanes Using Silica Gel as an Efficient and Recyclable Surface. Issue 3 (22nd January 2013) - Mendes, Samuel R.; Thurow, Samuel; Fortes, Margiani P.; Penteado, Filipe; Lenardao, Eder J.; Alves, Diego; Perin, Gelson; Jacob, Raquel G.
Abstract A simple solvent‐free protocol is developed.